Associations of maternal exposure to 41 metals/metalloids during early pregnancy with the risk of spontaneous preterm birth: Does oxidative stress or DNA methylation play a crucial role?. (January 2022) - Xu, Ruiwei; Meng, Xin; Pang, Yiming; An, Hang; Wang, Bin; Zhang, Le; Ye, Rongwei; Ren, Aiguo; Li, Zhiwen; Gong, Jicheng
Graphical abstract: Highlights: Maternal exposure to Mn, Fe, Cu, Nd, Hg, and Pb during early pregnancy was positively associated with the risk of SPB. Maternal oxidative stress level was positively associated with exposure to Fe, Pr, Eu, Er, and Lu. Maternal DNA methylation levels were significantly associated with exposure to multiple types of metals/metalloids. Abstract: Background: Few studies have explored the effects of multiple types of metals/metalloids on spontaneous preterm birth (SPB). A nested case–control study was conducted in Shanxi Province to investigate the associations between maternal exposure to 41 metals/metalloids during early pregnancy and the risk of SPB, and to clarify the underlying mechanisms of oxidative stress and DNA methylation. Methods: A total of 74 controls with full-term delivery and 74 cases with SPB were included in the nested case–control study. The metals/metalloids in serum and the DNA adducts in peripheral blood cell DNA were determined using ICP-MS and UPLC-QqQ-MS/MS, respectively. Unconditional logistic regression models were employed to estimate the associations of the risk of SPB with the metal concentrations, as well as with the levels of oxidative stress/DNA methylation. In addition, linear regression models were used to investigate the associations between the metal/metalloid concentrations and the levels of oxidative stress/DNA methylation. Results: After adjusting for potential confounders, the concentrations of Mn, Fe, Cu, Nd, Hg, and Pb in maternal serum during early pregnancy were positively associated with the risk of SPB. Compared with the lowest levels (Quartile 1) of Mn, Fe, Cu, Nd, Hg, and Pb, the odds ratios of SPB increased to 5.21 (95% CI: 1.63, 16.68), 3.47 (95% CI: 1.07, 11.21), 16.23 (95% CI: 3.86, 68.18), 10.54 (95% CI: 2.79, 39.86), 5.88 (95% CI: 1.72, 20.11), and 4.09 (95% CI: 1.31, 12.77) in the highest levels (Quartile 4), respectively. A significant increase in 8-OHdG was associated with the increased exposure to Fe, Pr, Eu, Er, and Lu. The levels of 5-MdC, 5-HmdC, and N6-MdA—the indicators of DNA methylation—were associated with exposure to multiple metals/metalloids. However, no significant associations were observed between the levels of oxidative stress or DNA methylation and the risk of SPB. Conclusions: Exposure to multiple types of metals/metalloids during early pregnancy is positively associated with the risk of SPB. Oxidative stress and DNA methylation are significantly associated with exposure to multiple metals/metalloids. Systemic oxidative stress and DNA methylation have not been proven to be the mediating mechanisms of metals increasing the risk of SPB.